Alterações fisiológicas e bioquímicas em quatro espécies florestais do bioma caatinga submetidas a alagamento - Ferreira, Débora Teresa da Rocha Gomes (2011)
The Brazilian Northeast presents, for the most part, a semi-arid climate, hot and dry. This region is predominantly occupied by the Caatinga biome characterized by presence of xerophytic vegetation, with variety of physiognomy and floristic. Part of the São Francisco River Basin in the states of Alagoas and Sergipe, is part of this biome. However, this presents little knowledge of vegetation component and advanced levels of environmental degradation. For its recovery is essential knowledge of the species ecophysiology to be used for revegetation of the basin areas and especially in marginal areas of the waterways of the Caatinga. Thus, this study aimed to investigate the behavior of species that occur in the Caatinga biome, compared to soil flooding (stress anoxic / hypoxic) in order to indicate the same for revegetation of the marginal areas of the waterways of the Caatinga. Seedlings of Tabebuia aurea, Caesalpinia ferrea, Aspidosperma pyrifolium and Bauhinia forficata, with five months of age were subjected to soil flooding permanent or temporary (flooding followed by drainage). For the flood water depth was maintained between 10-20 mm above ground level. Throughout the experiment we evaluated the fluorescence emission of chlorophyll, before dawn (Fv / Fm) and midday (Fv / Fm and Yield) and chlorophyll content in the third leaf fully developed, using a portable fluorometer modulated light and the SPAD, respectively. At the end of the experiment was determined leaf water potential and chlorophyll (a, b and total), the accumulation of soluble sugars, proline, total amino acids, proteins and activity of the enzyme alcohol dehydrogenase (ADH) (newer roots). It was also accompanied the growth of plants during the experiment determining the height, diameter and number of leaves, every four days, and at the end of the experiment the leaf area, biomass accumulation and distribution. Stress reduced the quantum efficiency of photosystem II and SPAD reading in all the seedlings of the species studied, with recovery in these variables when the plants were removed from the stress. Flooding reduced chlorophyll content only in the seedlings of A. pyrifolium and B. forficata subject to flooding. The seedlings of C. ferrea flooded had increased the content of chlorophyll b; however this was reduced in A. pyrifolium and B. forficata the same treatment. The total chlorophyll content was reduced by lack of oxygen only in seedlings of C. ferrea. The four species showed increases in response to stress, in the variables carbohydrate and protein. There was a reduction from plants subjected to flooding in the growth analysis and leaf water potential. The results allowed inferring that T. aurea and B. forficata develop mechanism of tolerance to flooding and better recovery when removed from the stress.